Libya: Getting serious about negotiations. How a new political process could help tackle security challenges - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2018)
Libya's longstanding political deadlock reached breaking point with the fighting between rival militias in Tripoli in September 2018. Throughout the preceding two years of political stalemate, the UN-led approach to negotiations remained vested in defunct institutions that blocked any progress. As a result, there was no prospect for the formation of regular security forces under government control, let alone the unification of Libya's divided security institutions. Addressing these security challenges requires a new push for a transitional power-sharing agreement with a roadmap towards elections. Negotiations need to involve actors with influence on the ground, including representatives of armed groups. Such a push should also include talks over new security arrangements in Tripoli, as well as efforts at reunifying economic institutions.
Keywords: 320